Multiple acute complications of transarterial chemoembolization of liver metastases - R. N. Abu Shamsia; Yu. M. Zakharash (Сучасні медичні технології)
The aim of the work: to describe a clinical case of treatment of multiple acute complications after transarterial chemoembolization of liver metastases in a patient with pancreatic cancer.